An examination of the literary quality of two reading schemes - Waters, Nigel Bruce (Rhodes University, Faculty of Education, Department of Education, 1988)
Learning to read is one of the most crucial life tasks that the young child must acquire whilst in primary school. In modern society, much of what one does is dependant on having the ability to read. While a great deal of research has focused on how children learn to read, relatively little attention has been paid to the literary quality of the material the children are exposed to whilst learning to read. In the past few years I have become increasingly concerned with the number of teachers who use material designed for teaching children to read without being aware of the literary quality of the material. While numerous teachers are aware of the issues surrounding the learning to read debate and use up to date materials to teach reading, far too many accept the material supplied by the school without questioning its literary merit and its impact upon the young reader. This piece of research is an attempt to evaluate the literary quality of two reading schemes currently in use in Cape Education Department schools. The chief conclusion of the research is that the schemes examined fall far short of the standards required for them to be considered good literature. Although the research is limited to two reading schemes, it is hoped that a teacher using other schemes could use the framework supplied in this study to examine the literary quality of the material she is using. Furthermore, the final chapter offers suggestions as to how to replace material of poor literary quality with books of a higher literary standard. On the basis of the above findings it is suggested that there is a need for individual teachers, schools, teacher training institutions and the Cape Education Department to examine the literary quality of reading schemes and books that are used in the process of teaching children to read. It is hoped that this piece of research will create a greater awareness amongst teachers of the literary quality of reading materials and prompt further research into such materials that will be of benefit to the central character in this study; the young child learning to read
Keywords: Reading (Primary); Reading -- Language experience approach; Readability (Literary style)